Analisis Indeks Kekeringan Meteorologis Lahan Gambut Di Pulau Bengkalis - Sinta Afdeni; Sigit Sutikno; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This study analyzed meteorological drought in peatlands area using Tropical Rainfall Measuring Mission (TRMM) rainfall satelit data. Bengkalis Island, Indonesia was picked up as study area of this research because Bengkalis area is vulnerable against peat fire. The index of meteorological drought was analyzed using Standardized Precipitation Index (SPI) method based on Geographic Information System (GIS). The period of calculation were conducted on monthly and half monthly period. The result it was found that the SPI dryness index in each grid was almost the same or had no significant difference, where there was no dry and wet period simultaneously in the same time period. In the half monthly period, the lowest SPI score was -4,710 and the highest SPI was 1.903. While in monthly period, the lowest SPI value is -2,806 and the highest SPI value is 1,914. Keywords: meteorological drought index, SPI, TRMM, GIS